Cumulative trauma and neuropsychological functioning: examining the role of resilience - Essert, Deborah Pratt, author; Conner, Bradley T., advisor; Chavez, Ernest, committee member; Davalos, Deana B., committee member; Biringen, Zeynep, committee member (Colorado State University. Libraries, 2017)
Previous research has linked childhood trauma to a range of adverse psychological and behavioral consequences which affect a child's wellbeing and ability to be successful socially and academically. Previous studies have also found childhood trauma to be associated with deficits in neuropsychological functioning. It has been proposed that the experience of trauma at critical points disrupts a child's neurodevelopment and that the disruption and subsequent deficits in neuropsychological functioning in part explain the psychological and behavioral struggles exhibited by traumatized children. This study aimed to explore the relation between cumulative trauma and psychological, behavioral, and neuropsychological outcomes among system-involved youth. Resilience and age at onset were included in analyses as potential mediators. Results indicated that more trauma types experienced predicted more psychological symptoms, and more behavioral concerns among youth living with their biological parents. In addition, deficits in executive function, specifically in shifting, were predicted by cumulative trauma. These results demonstrate the importance of accounting for the number of traumas experienced by youth present with related symptoms and behavioral concerns, and highlight the need to continue to explore the influence of cumulative trauma on neuropsychological function.
Keywords: trauma; neuropsychology